Tirbanibulin 1% Ointment Significantly Reduces the Actinic Keratosis Area and Severity Index in Patients with Actinic Keratosis: Results from a Real-World Study - Kirchberger, Michael; Gfesser, Michael; Erdmann, Michael; Schliep, Stefan; Berking, Carola; Heppt, Markus (Journal of Clinical Medicine, 2023)
Background: Actinic keratosis (AK) is a cutaneous lesion resulting from the proliferation of atypical epidermal keratinocytes caused by long-term exposure to ultraviolet radiation. AK may progress to cutaneous squamous cell carcinoma (cSCC) and therefore is often treated with topical agents such as 5-fluorouracil, diclofenac, imiquimod, and photodynamic therapy. Tirbanibulin has been approved based on two phase III trials in the USA. However, real-world evidence for tirbanibulin is absent. Methods: This was a single-centre study of adult patients with clinically typical, visible AK on the face or scalp treated with tirbanibulin 1% ointment. Treatment was administered as per label once daily for 5 consecutive days on the same lesions or field. Treatment outcomes were assessed 4 weeks after treatment, with additional optional assessments conducted at later time points. Efficacy was measured using the actinic keratosis area and severity index (AKASI) and digital dermoscopy. Results: A total of 33 patients were treated of whom 30 were analysed. The median AKASI score was 5.6 (1.4–11) pre-treatment and 1.2 (0–7.4) post-treatment (p < 0.0001). Complete clearance as defined by AKASI scores less than 1 was achieved in 47% (n = 14) and 57% (n = 13) at the first and second follow-up, respectively. All local reactions resolved spontaneously and without sequelae. The most common local reactions were erythema (80%, n = 26) and flaking or scaling (43%, n = 13). Conclusions: Tirbanibulin 1% ointment significantly and rapidly reduced the AKASI score in a real-world setting. The complete clearance rates were in line with those observed in the two pivotal trials.
CRIS-Team Scopus Importer:2023-08-11
Keywords: actinic keratosis; AKASI score; Klisyri